Perceiving Collision Impacts in Alzheimer’s Disease: The Effect of Retinal Eccentricity on Optic Flow Deficits - Kim, Nam-Gyoon (Frontiers in Aging Neuroscience, 2015)
The present study explored whether the optic flow deficit in Alzheimer’s disease (AD) reported in the literature transfers to different types of optic flow, in particular, one that specifies collision impacts with upcoming surfaces, with a special focus on the effect of retinal eccentricity. Displays simulated observer movement over a ground plane toward obstacles lying in the observer’s path. Optical expansion was modulated by varying tau-dot. The visual field was masked either centrally (peripheral vision) or peripherally (central vision) using masks ranging from 10° to 30° in diameter in steps of 10°. Participants were asked to indicate whether their approach would result in “collision” or “no collision” with the obstacles. Results showed that AD patients’ sensitivity to tau-dot was severely compromised, not only for central vision but also for peripheral vision, compared to age- and education-matched elderly controls. The results demonstrated that AD patients’ optic flow deficit is not limited to radial optic flow but includes also the optical pattern engendered by tau-dot. Further deterioration in the capacity to extract tau-dot to determine potential collisions in conjunction with the inability to extract heading information from radial optic flow would exacerbate AD patients’ difficulties in navigation and visuospatial orientation.